2018
DOI: 10.1200/jco.2018.36.15_suppl.1049
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life (HRQoL) in MONARCH 2: Abemaciclib plus fulvestrant in women with HR+, HER2- advanced breast cancer (ABC) who progressed on endocrine therapy.

Abstract: Background In the phase III MONARCH 2 study (NCT02107703), abemaciclib plus fulvestrant significantly improved progression‐free survival (PFS) versus placebo plus fulvestrant in patients with hormone receptor‐positive (HR+), HER2‐negative advanced breast cancer (ABC). This study assessed patient‐reported pain, global health‐related quality of life (HRQoL), functioning, and symptoms. Materials and Methods Abemaciclib or placebo (150 p.o. mg twice daily) plus fulvestrant (500 mg, per label) were randomly assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…1). Furthermore, this higher symptom burden of nausea, vomiting, appetite loss, diarrhea, and systemic therapy side effects was more likely to be reported by patients in early visits while on treatment . Dose reductions or omissions and symptom‐specific treatment (i.e., antidiarrheal medication) were effective at reducing these symptoms to baseline or near‐baseline levels at later study visits and at follow‐up for diarrhea .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…1). Furthermore, this higher symptom burden of nausea, vomiting, appetite loss, diarrhea, and systemic therapy side effects was more likely to be reported by patients in early visits while on treatment . Dose reductions or omissions and symptom‐specific treatment (i.e., antidiarrheal medication) were effective at reducing these symptoms to baseline or near‐baseline levels at later study visits and at follow‐up for diarrhea .…”
Section: Resultsmentioning
confidence: 97%
“…Although this study found a higher symptom burden over time in the abemaciclib arm compared with the control arm, as measured in change from baseline for nausea and vomiting, appetite loss, and systemic side effects, these symptoms did not meet the criteria for clinically meaningful differences. Furthermore, for all symptoms, this burden was reported during early study visits and returned to baseline or near‐baseline levels for most patients .…”
Section: Discussionmentioning
confidence: 93%
“…54 Data recently presented from MONARCH-2 using the EORTC QLQ-C30, BR-23, and Brief Pain Inventory short form showed no significant difference in HRQoL between the two treatment groups; however diarrhea, appetite loss, and nausea/vomiting were worse in the abemaciclib arm. 55 These data were not specific to older patients. Further analysis indicated appetite loss and nausea/vomiting were worse with early cycles and returned to near baseline after cycle 7, whereas diarrhea returned to near baseline post-treatment.…”
Section: Abemaciclibmentioning
confidence: 90%
“…In this latter, no significant differences in HRQoL, using the EORTC QLQ-C30, BR-23, and Brief Pain Inventory short form, were observed between the two arms. 56 However, diarrhea, appetite loss, nausea, and vomiting were worse in the abemaciclib group.…”
Section: How To Select the Cdk 4/6 Inhibitor In Clinical Practice?mentioning
confidence: 94%